2009
DOI: 10.2337/dc09-0071
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Depressive Symptoms and Glycemic Control in Type 2 Diabetes

Abstract: OBJECTIVETo compare whether depressive symptoms are more strongly related to subsequent or prior glycemic control in type 2 diabetes and to test whether patient characteristics modify these longitudinal associations.RESEARCH DESIGN AND METHODSOn two occasions separated by 6 months, depressive symptoms and glycemic control were assessed in 253 adults with type 2 diabetes. Regression analyses examined depressive symptoms as both a predictor and outcome of glycemic control and tested whether medication regimen (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 20 publications
10
50
1
Order By: Relevance
“…16,30], and a number of studies support this hypothesis regarding both outcomes, self-management behaviour [31] and glycaemic control [32][33][34].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…16,30], and a number of studies support this hypothesis regarding both outcomes, self-management behaviour [31] and glycaemic control [32][33][34].…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…However, pooled data from cross-sectional studies of depressive symptoms and glycaemic control have found only a small effect size (d = 0.17) [8]. From the few prospective studies published, the evidence for an association between depressive symptoms and glycaemic control is also weak [9][10][11][12][13]. While treatments for depressive symptoms usually improve depressive symptoms [14,15], they do not always improve glycaemic control, unless integrated with additional support in diabetes management [16].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depressive symptoms and diabetes distress are known to increase with diabetes duration [24,25], an important confounder that limits the interpretation of previous studies of the effects of depression and diabetes distress on self-management and glycaemic control [11,26]. Studying these potential effects at the time of diagnosis of type 2 diabetes is a methodologically robust approach, as there is minimal confounding by long duration of type 2 diabetes and it is an important window of opportunity for interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with ITDM are more vulnerable to depression and their depression is more severe than persons with NITDM [15]. This interaction of insulin treatment and depression could result in persons on insulin treatment being more likely to be hospitalized and to stay in the hospital longer for the depression treatment [11][12][13]15]. Future research is needed to examine how insulin treatment impacts depression treatment in this population.…”
Section: Discussionmentioning
confidence: 99%
“…These persons need to closely monitor blood glucose and manage insulin use on a daily basis and are, perhaps, more vulnerable to diabetes-related depression [11][12][13][14], and have worsening depressive symptoms (among those with MDD) [15]. Because of the severity of depression, persons with ITDM may be vulnerable to self-monitoring their blood glucose less frequently than they should [16] and to subsequent diabetes complications [11,15]. Thus, excess costs are very likely to be influenced by the interaction between depression and diabetes treatment mode [17].…”
Section: Introductionmentioning
confidence: 99%